2016
DOI: 10.1002/ijc.30433
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR‐122 and miR‐200 family are prognostic markers in colorectal cancer

Abstract: Circulating microRNAs (miRNAs) have been proposed as minimally invasive prognostic markers for various types of cancers, including colorectal cancer (CRC), the third most diagnosed cancer worldwide. We aimed to evaluate the levels of circulating miRNAs that might serve as markers for CRC prognosis and survival. We included plasma samples of 543 CRC patients with stage I-IV disease from a population-based study carried out in Germany. After comprehensive evaluation of current literature, 95 miRNAs were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 52 publications
3
77
0
Order By: Relevance
“…Moreover, miR‐122‐5p was potential regulator of several BC‐correlated targets such as ADAM10, Syndecan‐1 and IGF1R . The diagnostic or prognostic value of circulating miR‐122 was also reported in other cancers such as colorectal cancer and non‐small cell lung cancer, indicating its close connection with tumor biological processes . Circulating miR‐215 was previously found to be decreased in plasma in progressive BC patients in comparison with those who did not, but van Schooneveld et al showed just the opposite result of increasing tendency in serum in metastatic BC patients .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR‐122‐5p was potential regulator of several BC‐correlated targets such as ADAM10, Syndecan‐1 and IGF1R . The diagnostic or prognostic value of circulating miR‐122 was also reported in other cancers such as colorectal cancer and non‐small cell lung cancer, indicating its close connection with tumor biological processes . Circulating miR‐215 was previously found to be decreased in plasma in progressive BC patients in comparison with those who did not, but van Schooneveld et al showed just the opposite result of increasing tendency in serum in metastatic BC patients .…”
Section: Discussionmentioning
confidence: 99%
“…A number of different microRNAs have been shown to be differentially expressed in patients with CRC versus healthy controls. 45,53 Variability in the timing of serum sampling may be an important factor. 55 miR-200c was individually shown to have good predictive values in the diagnosis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Some of this variation may be accounted for by, as the authors comment, the fact that the some of the blood samples were hemolyzed and that phlebotomy was performed at variable time-points in relation to the date of surgery and to adjuvant therapy 53. High plasma expression of miR-200a was associated with worse OS in patients with metastatic CRC (HR 5 1.227, 95% CI: 1.008-1.495, p 5 0.042).…”
mentioning
confidence: 99%
“…Miyoshi et al, 6 who reported miR-139-5p upregulation in the serum samples of recurrence-positive CRC patients, added 25 fmol of cel-miR-39 to each sample for data normalization. Maierthaler et al, 10 who revealed that increased plasma levels of miR-122 were associated with a poor prognosis and a shorter survival in CRC patients, added 3.5 µL of cel-miR-39 (1.6 × 10 8 copies/µL) to plasma samples for data correction. Nonaka et al, 8 who identified miR-199a-3p as a novel serum biomarker for CRC, added 20 fmol of cel-miR-39 to each sample to manage sample-to-sample variations.…”
mentioning
confidence: 99%